Estimating the effective population size of Swedish native cattle : understanding the demographic trajectories of indigenous Swedish cattle breeds - Adepoju, Dolapo (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2022)
The indigenous cattle populations are on the decline globally with the continuous improvement of genetic gains in commercial breeds. Due to their unique adaptive features to the local ecosystem, traditional cattle breeds are pools of valuable genetic resources that could help combat the impact of climate change in the near future. However, besides the census population sizes, it is crucial to assess the impacts of genetic drift to design strategic breeding programmes to improve genetic diversity and safeguard the breeds against genetic erosion. This study estimated the effective population sizes (Ne) of nine Swedish native cattle breeds from 147 individuals genotyped with GenSeek GGP Bovine 150K and 33 samples from whole-genome sequence data using the observed linkage disequilibrium spectrum. Demographic trajectories of up to 200 generations ago were also inferred to match the decline observed to a series of events that have shaped the breeds’ current status. The estimated result showed that two breeds (Bohuskulla and Väne) have Ne values within Ne ≤ 50, indicating critical status. Also, four are in the endangered zone (Ringamålako, Fjällnara, Swedish Polled, and Swedish Red Polled) with Ne ≤ 100, and only three breeds (Holstein Friesian, Swedish Red Cattle, and Swedish Mountain Cattle) are considered stable to limit total fitness loss up to 10% with Ne ≥ 100. Also, a general dramatic decline was observed between the 12th to 15th generations across all breeds, which suggests that the reduction in the population of Swedish native cattle breeds began with breed formation. While maintaining high Ne is critical for the conservation of indigenous cattle, using the pedigree method or demographic might not provide accurate estimates due to several limitations. These include overlapping generations and a lack of pedigree information. Therefore, besides preventing inbreeding, Ne estimates from genomic data should be adopted in the breeding and conservation strategies of Swedish native cattle breeds. They are non-dependent on pedigree information and demographic data.